2016
DOI: 10.1155/2016/5608518
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mucosa-Associated Lymphoid Tissue Lymphoma of Thyroid with the Serial Ultrasound Findings

Abstract: Extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT) of the thyroid gland is uncommon. Even though its natural history is not well defined, it is known to be indolent course. We present a case of primary MALT thyroid lymphoma with the serial sonographic findings in the patient presenting as the focal nodule. A 45-year-old woman visited our hospital for neck examination. Initially, fine-needle aspiration cytology in the focal hypoechoic lesion in the left thyroid lobe on ultrasound sono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The study also stated that the incidence of Hashimoto's thyroiditis differed significantly among the four lymphoma groups: MALT, DLBL, MALT + DLBL, and small lymphocytic lymphoma (P=0.014) (11). Although most cases have Hashimoto's thyroiditis in the background, it has been reported that MALT lymphoma can also develop as de novo without the presence of the former (12).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The study also stated that the incidence of Hashimoto's thyroiditis differed significantly among the four lymphoma groups: MALT, DLBL, MALT + DLBL, and small lymphocytic lymphoma (P=0.014) (11). Although most cases have Hashimoto's thyroiditis in the background, it has been reported that MALT lymphoma can also develop as de novo without the presence of the former (12).…”
Section: Discussionmentioning
confidence: 83%
“…The diagnosis of extranodal marginal zone lymphoma may be delayed due to poor systemic symptoms. The occurrence of B symptoms and cytopenia is very rare in this disease (11,12). Hematological tests along with few additional tests are required for patients with MALT lymphoma that are standard for patients with NHL required at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general imaging manifestations of MALT lymphoma are solitary or multiple solid homogeneous masses without cysts, necrosis or calcification[ 15 , 16 ]. The ultrasound features of MALT lymphoma could be described as interspersed linear echogenic strand patterns or segmental patterns, according to the thicknesses of the septa[ 17 ]. The pathological basis for the formation of linear echo may be the expansion of lymphoma cells bordered by fibrous bands.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 - 5 ] It is postulated to occur as a response to autoimmune processes, such as in patients with Hashimoto thyroiditis and patients with Helicobacter pylori infection. [ 6 ] FNA would show thyroid follicular atrophy with Hurthle cell changes and follicular cells with lymphocytic infiltration as lymphoepithelial structures [ 7 ] which were not detected in the current case (option C). Primary squamous cell carcinoma, typically common in elderly patients, is a rare entity which carries poor prognosis (may be a component of anaplastic thyroid carcinoma).…”
Section: Questionmentioning
confidence: 95%